2017
DOI: 10.1123/pes.2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Effects on Metabolic Function Among Youth: A Systematic Review

Abstract: Purpose: This systematic review evaluates the relationship between resistance training and metabolic function in youth. Methods: PubMed, Embase, Cochrane Library, Web of Science, CINAHL, and ClinicalTrials.gov were searched for articles that: (1) studied children; (2) included resistance training; (3) were randomized interventions; and (4) reported markers of metabolic function. The selected studies were analyzed using the Cochrane Risk-of-Bias Tool. Results: Thirteen articles met inclusion criteria. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…It is well-established that physical activity improves cardiometabolic risk factors in children and adolescents [ 4 , 6 , 48 ]. In epidemiological studies, physical activity is often operationalized by MVPA which is frequently derived by counting time spent at or above 2000 to 3200 cpm in youth [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that physical activity improves cardiometabolic risk factors in children and adolescents [ 4 , 6 , 48 ]. In epidemiological studies, physical activity is often operationalized by MVPA which is frequently derived by counting time spent at or above 2000 to 3200 cpm in youth [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review confirmed the associated health benefits of meeting the recommended MVPA guideline [5]. Furthermore, participating in the recommended 3 days of MBSE per week has also been associated with positive physical and mental health benefits in children and young people [6][7][8][9][10]. Despite this evidence, less than 50% of young people in Europe meet the recommended amount of MVPA suggested by the World Health Organisation (WHO), with this figure declining with age [11].…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…However, it was noted that these values returned to baseline 6 months after the end of the training regimen suggesting the need to continue physical activity to maintain gains in both fitness and self-esteem. It is also hypothesized that introducing overweight, obese and sedentary adolescents to RT can also be used to help acclimate youth to physical exercise in a less strenuous and intimidating way that eventually builds to more vigorous and regular cardiovascular exercise (12).…”
Section: Benefits Of Rtmentioning
confidence: 99%